ANALYSIS OF FUNCTIONALLY GRADED GRAPHENE REINFORCED CIRCULAR PLATES SUBJECTED TO THERMO-MECHANICAL LOADS - MEI Jing; SHEN LuLu; YANG Bo (Jixie qiangdu)
Based on the generalized Mian and Spencer plate theory,the problem of graphene reinforced functionally graded circular plates subjected to concentrated force and temperature field is studied. By virtue of the modified Halpin-Tsai model,the effects of temperature dependence and defect size of graphene nanoplatelets on the Young’s modulus of graphene reinforced composites are considered. Three kinds of distributions of graphene nanoplatelets（ GPLs） along the thickness direction are studied. When the circular plate is subjected to a concentrated force at the center,the problem is transformed into that of an annular plate subjected to uniformly distributed shear forces along the inner boundary. The nonlinear temperature field caused by heat conduction is considered along the thickness direction of the plate. Through comparison with available results in the numerical example,the validity of the method in this paper is verified,and the influences of GPL distribution,defect size,temperature field and boundary conditions on the thermoelastic response of circular plates are discussed.